PENGARUH PENGGUNAAN KOMBINASI CATHER (UREA POWDER DAN MELAMIN POWDER) PADA PEREKAT MELAMIN FORMALDEHIDA TERHADAP KETEGUHAN REKAT DAN EMISI FORMALOEHIDA KAYU LAPIS KERUING (Dipterocarpus lowii hook f) - Darni Subari (Jurnal Hutan Tropis, 2011)
This study aims to determine the firmness of the resulting plywood sticking when given catcher powdered urea and melamine powder in mortar. Expected to be emitted as small as possible with the persistence of high-sticking adhesive. The method used is the method of factorial experiment with Completely Randomized Design with two replications. There are two factors which are the composition factors of treatment given urea powder (A1 = 0 g, A2 = 5 gr, A3 = 10 gr, 15 gr = A4, and A5 = 20 g) B1, and the composition of melamine powder factor (= 0 g, B2 = 3 g, 6 g = B3, B4 and B5 = 9 g = 12 g). The results show (1) testing the waters did result in the amount, not too much difference with control (A1B1) also merge a and b did not make a significant impact, but the water content is in this study does not exceed 12%. (2) Plywood results of this study are based on a combination of persistence, stick around to meet the quality requirements of Japanese plywood (JPMA) 1973, that the above 7 kg/cm2. (3) determination of the adhesion occurs in the study, with the addition of chather still above 1973 but JPMA melamine content standards in this case, while not significantly affect both urea and interaction effect is very real. (4) based on plywood formaldehyde emission results of this study, most combination treatments to meet the requirements, with the addition of melamine powder shall not be compensated by adding urea powder, radiation treatment will be higher than A1B1..Keywords : Catcher, plywood, emission